Aceh’s Halal Tourism as the Instrument to Increase Indonesia’s Economy by Attracting Foreign Tourism - Farah Ghina Fadhilah; Isnashella Pertiwi Widyastuti; M Fawwaz Syafiq Rizqullah (Gorontalo Development Review, 2020)
The aim of the research in this paper was to examine the prospect of halal tourism in Nanggroe Aceh Darussalam province as the instrument of Indonesia’s soft diplomacy in increasing international cooperation that affects Indonesia’s economy. The reason behind this research conduct was due to the myriad of Indonesia halal tourism as destination which had earned several achievements in the context of the ‘World's Most Popular Halal Tourism Destinations’ by the Global Muslim Travel Index (GMTI). Aceh became one of the provinces in Indonesia that is made as the focus of halal tourism development and has won two prestigious awards at the World Halal Tourism Award. By using the theory of soft diplomacy by Joseph S. Nye, Jr., and Qualitative data approach from journal, book, and other credible resources, this article found that Aceh can be a unique and appealing halal tourism area that can become a medium for Indonesia’s soft diplomacy in conducting international cooperation, especially with others Islamic countries in the world. Therefore, it can increase Indonesia's domestic economy significantly, especially to Aceh province, which will eventually give a significant impact to Indonesia’s national economy.